Effective communication model for Software Development Project in Ambersoft / Fatin Noor Amylia Abdul Muluk - Abdul Muluk, Fatin Noor Amylia (2017)
The effective communication model for software development project in Ambersoft is a research project that assists project manager and project leader to communicate effectively. The problem occur when the meaning of the message fail to delivered same as sender’s understanding due to ineffective communication. Besides that, communication is very important in a project because poor communication is the reason most IT projects fail. According to some studies, the problem with communication in IT project can be reduced by using a model of communication. Therefore this research aim is to develop an effective communication model for software development project in Ambersoft. In order to achieve the research’s aim, the qualitative method is used to support and complement result and finding. Through data gathering phase all the practices for communication will be adopted into the chosen existing communication model. Therefore, the finding for this research is effective communication model for software development project in Ambersoft was developed and evaluated. For future works, there are a few improvements that can be done to gain a better result such as involves more IT companies to conduct an interview and involves more people to evaluate the communication model.